Anchoring and Adjustment Bias in Working Capital Management and Performance of Small and Medium Enterprises (SMEs): The perspectives of Ghanaian SMEs Managers - Jeff, Lamptey; Asri, Marsidi (Human Resource Management Academic Research Society, 2020)
This paper explored Anchoring and Adjustment in working capital management and performance of small and medium-sized enterprises (SMEs) in Accra, Ghana. We adopted a qualitative case study design and employed in-depth interviews to obtain data from thirty-five (35) managers drawn from trading manufacturing sectors. We found that SME managers(owners) primarily rely on selfgenerated and provided anchor. More specifically, managers anchor on customer’s trust, price list and quotation, current and past sales trends which results to overinvestment and underinvestment in working capital and higher or lower performance. Therefore, we conclude that anchoring and adjustment in working capital management and performance matter